Perbandingan Kajian Muslim dan Orientalis - Aisyah Nurul Aini; Muhammad Rajab Al Fathin Nasution; Sulidar (Al-Qolamuna: Journal Komunikasi dan Penyiaran Islam, 2026)
This article comprehensively examines the comparison between Muslim studies and Orientalist studies in Islamic studies, positioning them as two scholarly traditions with distinct characteristics, orientations, and academic implications. The main focus of the discussion includes the objects and perspectives of research, the methodologies and approaches used, and the impact and reactions of each tradition on the development of Islamic studies. Muslim studies depart from an internal (insider) perspective, grounded in a normative-faith foundation and utilizing the Qur'an and Sunnah as primary sources of knowledge. Within this framework, Islam is understood not only as an object of scientific study but also as a transcendent system of values ​​and guidelines for life. In contrast, Orientalist studies developed within the Western academic tradition with an external (outsider) perspective, viewing Islam as a historical, social, and cultural phenomenon. The approaches used tend to be historical-critical, philological, and socio-humanities, with an emphasis on textual analysis, historical context, and the dynamics of Muslim society. Through a descriptive-analytical and comparative approach, this article demonstrates that Orientalist studies often draw criticism, particularly regarding colonial bias, normative reduction of meaning, and a tendency toward generalization. The results of this study demonstrate that the contributions of Orientalists to the development of scientific methodology, source criticism, and the expansion of Islamic studies literature cannot be ignored. Furthermore, Muslim studies play a strategic role in strengthening religious identity, maintaining the authority of Islamic sources, and encouraging a renewal of Islamic thought that is more contextual and responsive to the challenges of the times. By critically and proportionately bringing these two traditions together, this article emphasizes the importance of open, respectful, and civilized academic dialogue to enrich the treasury of contemporary Islamic studies. Abstrak Artikel ini mengkaji secara komprehensif perbandingan antara kajian Muslim dan kajian orientalis dalam studi Islam, dengan menempatkan keduanya sebagai dua tradisi keilmuan yang memiliki karakter, orientasi, dan implikasi akademik yang berbeda. Fokus utama pembahasan meliputi objek dan perspektif penelitian, metodologi dan pendekatan yang digunakan, serta dampak dan reaksi yang ditimbulkan oleh masing-masing tradisi dalam perkembangan studi Islam. Kajian Muslim berangkat dari perspektif internal (insider), yang berpijak pada landasan normatif-keimanan dan menjadikan Al-Qur’an serta Sunnah sebagai sumber utama pengetahuan. Dalam kerangka ini, Islam dipahami tidak hanya sebagai objek kajian ilmiah, tetapi juga sebagai sistem nilai dan pedoman hidup yang bersifat transenden. Sebaliknya, kajian orientalis berkembang dalam tradisi akademik Barat dengan perspektif eksternal (outsider), yang memandang Islam sebagai fenomena sejarah, sosial, dan budaya. Pendekatan yang digunakan cenderung bersifat historis-kritis, filologis, dan sosial-humaniora, dengan penekanan pada analisis teks, konteks sejarah, serta dinamika masyarakat Muslim. Melalui pendekatan deskriptif-analitis dan komparatif, artikel ini menunjukkan bahwa kajian orientalis kerap menuai kritik, terutama terkait bias kolonial, reduksi makna normatif, dan kecenderungan generalisasi. Hasil dari penelitian ini menujukkan bahwa , kontribusi orientalis dalam pengembangan metodologi ilmiah, kritik sumber, serta perluasan literatur studi Islam tidak dapat diabaikan. Di sisi lain, kajian Muslim memiliki peran strategis dalam memperkuat identitas keagamaan, menjaga otoritas sumber-sumber Islam, serta mendorong pembaruan pemikiran Islam yang lebih kontekstual dan responsif terhadap tantangan zaman. Dengan mempertemukan kedua tradisi ini secara kritis dan proporsional, artikel ini menegaskan pentingnya dialog akademik yang terbuka, saling menghargai, dan berkeadaban guna memperkaya khazanah studi Islam kontemporer